Compliance of Anemia Prospective Brides in Consuming Blood Enhancement Tablets in Kalibaru Village, Cilincing District - Redjeb, Rusmini; Handayani, Sarah (PROMOTOR, 2025)
Study This aiming For analyze level compliance candidate bride woman (candidate) bride and groom) with anemia in consume additional tablets blood in the Village Kalibaru, District Cilincing, North Jakarta Approach qualitative used through technique interview with candidate bride, groom, family and officiant health Qualitative methods This chosen Because study This aiming For understand experience and perception candidate bride woman with anemia in consume additional tablets blood, and For identify factors that influence compliance them Information got from prospective brides and grooms, their partners, families and health workers in the Kelurahan area new times In research This analysis thematic used For identify factors that influence compliance candidate bride in consume additional tablets blood Research results show that compliance candidate bride influenced by the level understanding, effect side consumption, and support environment around The main obstacle covering discomfort moment taking tablets and lack of education Solutions found involving strengthening education, support couples and families, as well as monitoring periodically by officers health This study emphasize the importance of collaborative strategies in increase compliance candidate bride For prevent risk anemia and complications pregnancy With Thus, the education program based on community involving all party need implemented For support health reproduction in the region.